2022
DOI: 10.1111/jan.15195
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ experiences of accompanying patients dying during the COVID‐19 pandemic: A qualitative descriptive study

Abstract: Aims The aim was to explore nurses’ experiences of caring for and accompanying patients dying without the presence of family during the COVID‐19 pandemic. Design A qualitative descriptive design was used. Methods A purposive sample of registered nurses, caring for dying patients in Italian health‐care settings during the COVID‐19 pandemic, were selected. To capture a broad range of experiences, a maximum variety of participants about workplac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 39 publications
1
19
0
1
Order By: Relevance
“…Caregivers often stand in for the family in ensuring the best possible death during the last farewell, because of the visitation restrictions. ‘ I saw physicians cry … or that there was nothing more to be done, both for the older … ’ (Castaldo et al, 2022). Synthesized Finding 3: Caregivers show various emotions and mentalities. This synthesized finding was underpinned by 35 extracted findings and subdivided into 4 categories: ‘fear of contagion’, ‘pressure increase’, ‘negative emotions’ and ‘emotional exhaustion’, in that order.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Caregivers often stand in for the family in ensuring the best possible death during the last farewell, because of the visitation restrictions. ‘ I saw physicians cry … or that there was nothing more to be done, both for the older … ’ (Castaldo et al, 2022). Synthesized Finding 3: Caregivers show various emotions and mentalities. This synthesized finding was underpinned by 35 extracted findings and subdivided into 4 categories: ‘fear of contagion’, ‘pressure increase’, ‘negative emotions’ and ‘emotional exhaustion’, in that order.…”
Section: Resultsmentioning
confidence: 99%
“… Synthesized Finding 6: Affirmation of self‐worth. This synthesized finding was underpinned by 15 extracted findings and subdivided into 2 categories: ‘professional pride and sense of responsibilities’ and ‘trust in colleagues, managers and patients’. Seven studies have reported that caregivers express professional pride and a sense of duty (Bilal et al, 2020; Castaldo et al, 2022; Krok‐Schoen et al, 2021; Lingum et al, 2021; Morley et al, 2022; Sarabia‐Cobo et al, 2021; Sun et al, 2020). ‘ The people we serve; and, those we feel a great sense of responsibility for … ’ (Lingum et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of these changes are positive some have been challenging. The lack of human connection particularly during the COVID-19 pandemic has negatively impacted those needing care and those providing it (Castaldo et al, 2022;Holaday et al, 2022). Equally, mental health, health inequity and climate change are constant companions in a changing world.…”
mentioning
confidence: 99%